Jabatan Kerja Raya (JKR), Daerah Muar / Izzat Rais Ishak - Ishak, Izzat Rais (UiTM Cawangan Johor Kampus Pasir Gudang, 2018)
This report is set out to give the reader full information about my industrial training in Jabatan Kerja Raya (JKR) in Muar. Industrial training is one of the compulsory course in Universiti Teknologi Mara (UITM) which students need to complete whether in developer, consultant, construction, factory or company. This course is set up for students in order to give them experience and gain knowledge in working environment before going through the real working life. It also gives them an opportunity to apply the theories learned at the university to the real world of employment.